KERAJINAN CENDERAMATA KERAWANG GAYO DI KAMPUNG BEBESEN KECAMATAN BEBESEN KABUPATEN ACEH TENGAH - Oktaviani Oktaviani; Saniman Andi Kafri; Putri Dahlia (Educraf : Journal Of Craft Education, Craft Design And Creative Industries, 2023)
Gayo Kerawang Souvenir Crafts in Bebesen Village, Bebesen District is a cultural heritage that is still operating today which aims to maintain the culture of the typical Gayo community. Kerawang Gayo departs from symbols and as decorations that contain meaning in them. Along with the needs of human life, this Gayo Kerawang craft is growing in society according to the times. This study aims to find out how the form of Kerawang Gayo souvenirs in Bebesen Village, Bebesen District, Central Aceh Regency. The method used in this research is qualitative method. Techniques in data collection are observation, interviews and documentation. Researchers use the Dhasono Sony Kartika shape theory as a study in examining the shape of the souvenir. The products produced by souvenir craftsmen in Bebesen Village are bags, wallets, shirts, skirts, backpacks, table cloths, cushion covers, prayer rugs and others. These products are created according to market needs and tailored to the needs of consumer orders.